SHOCK EXPERIMENTS ON PRE-HEATED α- AND β-QUARTZ: II. X-RAY AND TEM INVESTIGATIONS - Langenhorst F. (My University, 1994)
Quartz single crystals pre-heated to different temperatures (20°, 275°, 540° and 630°C) were experimentally shocked to pressures ranging from 20 to 40 GPa, with the shock front propagating parallel to (10 0) or (0001). Shocked quartz pre-heated to 630°C is nearly X-ray amorphous at 26 GPa, while quartz shocked at room temperature still displays several X-ray diffraction lines up to 30 GPa. All samples that were still crystalline when shocked above 25 GPa exhibit lattice expansion, internal strain and reduced crystallite sizes. Lattice expansion was up to 1% for the constants ao and co and up to 3% for the cell volume, Vo. Quartz shocked parallel to (10 0) always shows larger lattice constants and is more strained than quartz shocked parallel to (0001), indicating that shock effects are controlled by the structural anisotropy. Internal strain is anisotropic, with minimum strain in the planes belonging to {10 2}.